EVALUASI PROGRAM ELIMINASI KUSTA PADA PENDERITA KUSTA DI PESISIR WILAYAH KERJA PUSKESMAS TAMILOUW KABUPATEN MALUKU TENGAH - Soulissa, Fathmy Fitriany; Sinay, Herlien; Dolang, Mariene Wiwin (Molucca Medica, 2024)
Leprosy is an infectious disease caused by Mycobacterium leprae, this disease can cause complex problems, not only in terms of medical such as physical disabilities but also to social, economic, cultural, security and national resilience problems. The development of negative stigma among the community about Leprosy Disease results in Leprosy Sufferers having to be able to face various complex problems to survive even though it has an impact on decreasing the quality of life and self-knowledge. Issues related to leprosy cases and the negative stigma received by leprosy sufferers, increasing and self-knowledge about leprosy are the keys that play an important role in the leprosy elimination program in sufferers so that an evaluation of the implementation of the leprosy elimination program is needed on the coast of Tamilouw village. This study is an observational qualitative study with a descriptive approach. The population in this study were all leprosy sufferers who lived in the work area of ​​the Tamilouw Health Center. The study was conducted in the work area of ​​the Tamilouw Health Center which organized the Elimination Program to reduce the number of leprosy sufferers. The informants in this study were 6 people. The results of the study showed that from the input aspect, namely the program can run well despite the limitations of human resources, funds and facilities, the process in implementing the program is in accordance with the SOP that has been determined by the Health Office, the output of monitoring and evaluation of program implementation has run well with reporting carried out once every three months. It is expected that the relevant Health Office will maximize funds for the implementation of the leprosy program so that input and processes that are not yet optimal can be overcome effectively and efficiently.